Factors affecting data quality of online questionnaires: Issues and metrics for sensory and consumer research. (December 2022) - Jaeger, Sara R.; Cardello, Armand V.
Highlights: Considers potential factors affecting data quality of online questionnaires. Identifies metrics to be used to evaluate data quality of online questionnaires. Advocates awareness/action on data quality among sensory/consumer researchers. Recommends practices to be adopted by sensory and consumer researchers. Abstract: Methodology used in sensory and consumer research has changed rapidly over the past several decades, and consumer research is now frequently executed online. This comes with advantages, but also with the potential for poor quality data due to uncontrolled elements of survey administration and execution. Published papers that utilize online data rarely report metrics of data quality or note precautions that were taken to ensure valid data. The aim of this paper is to raise awareness of the factors that influence online data quality. This is achieved by 1) identifying factors that can impact the reliability and validity of consumer data obtained with online questionnaires, 2) highlighting indices of online questionnaire data quality that can be used by researchers to assess the likelihood that their data are of poor quality, and 3) recommending a number of indices, counter-measures and best practices that can be used by sensory and consumer researchers to assess online questionnaire data quality and to ensure the highest degree of reliability and validity of their data. By making researchers aware of these sources of invalidity and by presenting available remedies and good practices, it is our intention that sensory and consumer scientists will adopt these measures and report them as a routine part of publishing online questionnaire data. Specific suggestions are offered regarding the important elements of data quality that should be included in scientific manuscripts.